Australia's nutrition transition 1961–2009: a focus on fats. Issue 3 (30th June 2015) - Naughton, Shaan S.; Mathai, Michael L.; Hryciw, Deanne H.; McAinch, Andrew J.
Abstract : Since the 1960s, Australian diets have changed considerably, influenced by a burgeoning multicultural cuisine, increase in urbanisation and food technology advances. This has been described as a 'nutrition transition', resulting in the adoption of a Western diet pattern, with a shift away from unrefined foods towards a diet higher in both plant-derived high PUFA and total fats and refined carbohydrates. Utilising the 1961–2009 annual food supply data from the UN FAO, the present study investigated changes in the intake of macronutrient and specific fatty acid in the Australian population, including that of the PUFA linoleic acid (LA), due to its hypothesised role in inflammation and risk for obesity. Cumulative change over time for the contribution of specific nutrients to total available energy (TAE) was calculated, as was linearity of change. Over the time period analysed, the cumulative change in TAE from carbohydrate was − 9·35 and +16·67 % from lipid. The cumulative change in TAE from LA was +120·48 %. Moreover, the cumulative change in the contribution of LA to total PUFA availability was +7·1 %. Utilising the average g/d per capita of LA from selected dietary sources, the change in the contribution of specific foodstuffs was assessed, with total plant oils having a cumulative change of +627·19 % to LA availability, equating to a cumulative change of +195·61 % in contribution to total LA availability. The results of the present study indicate that LA availability in Australia has increased over the previous five decades as a result of the availability of increased plant oils, as has total fat, possibly contributing to the increasing rates of obesity and obesity-associated co-morbidities.